Hemoadsorption in ‘Liver Indication’—Analysis of 109 Patients’ Data from the CytoSorb International Registry - Klementina Ocskay (MDPI AG, 2021)
Background: Our aim is to report the results of the ‘liver indication’ subset of patients in the CytoSorb International Registry. Methods: Structured data were recorded. Treatment characteristics and changes from T1 (start of hemoadsorption) to T2 (termination) were evaluated with a special focus on bilirubin, C-reactive protein, procalcitonin, interleukin-6, platelet levels, SOFA scores, mortality, and subjective assessment by the attending physicians. Results: Until January 2021, from the total 1434 patients, 109 (age: 49.2 ± 17.1 years, 57.8% males) received treatment for hyperbilirubinemia. APACHE II-predicted mortality was 49.6 ± 26.8%. In the study, 91% of patients were alive at the termination of hemoadsorption and improvement was observed by the physicians in 75 cases. Overall, 65 (59.6%) patients died in the hospital, and 60 (55.0%) died in the ICU. Patients received a median of two treatments for a median of 43 h (interquartile range: 24–72 h) in total. Serum bilirubin levels reduced significantly to −4.6 (95% CI: −6.329 to −2.8) mg/dL. Thrombocytopenia was reported in four patients as an adverse event. Conclusions: We report the largest case series on hemoadsorption for ‘liver indication’ from the CytoSorb International Registry. The finding of significant bilirubin removal observed in our study could have substantial impact in designing and executing further studies on the effects of hemoadsorption in liver dysfunction, which are certainly warranted.